High dives and parallel plans: Relationships between medical student elective strategies and residency match outcomes - Courneya, Carol Ann (Can Med Educ J, 2020)
BACKGROUND: Medical students are anxious about not getting a preferred residency position. We described elective patterns of two recent cohorts and examined associated match outcomes. METHODS: We conducted a retrospective review of the final-year electives of all students who participated in the residency match (first iteration) at one school for 2017 and 2018. We categorized elective patterns and associated them with aggregated match outcomes. We examined high-demand/low-supply (HDLS) disciplines separately. RESULTS: We described three elective patterns: High Dive, Parallel Plan(s), and No Clear Pattern. Many students had High Dive and Parallel Plans patterns; only a few showed No Clear Pattern. Match rates for High Dive and Parallel Plan patterns were high but many students matched to Family and Internal Medicine. When we separated out HDLS predominance, the match rate remained high but a significant number matched to disciplines in which they did not have a majority of electives. Most High Dive and Parallel Plan students who went unmatched did so with HDLS discipline electives. CONCLUSION: Many students chose High Dive and Parallel Plan strategies to both high-capacity and HDLS disciplines. Match rates were high for both patterns but students also matched to non-primary disciplines. Back-up planning may reside in the entire application, and not just electives selection.